Of apes and ancestors evolution, Christianity, and the Oxford debate - Hesketh, Ian, 1975- (Toronto [Ont.] : University of Toronto Press, 2009)
By reconstructing the Oxford debate of 1860 on the merits of Charles Darwin?s Origin of Species, and carefully considering the individual perspectives of the main participants, Ian Hesketh argues that personal jealousies and professional agendas played a formative role in shaping the response to Darwin's hypothesis.
Introduction -- Charles Darwin: historian of natural history -- The struggles of Soapy Sam -- Thomas Henry Huxley and Richard Owen: or, Darwin's bulldog and the queer fish -- Joseph Dalton Hooker and the early history of a great friendship -- The Oxford debate -- Remembering the Oxford debate -- Epilogue: the history of the present.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Huxley, Thomas Henry, -- 1825-1895.; Wilberforce, Samuel, -- 1805-1873.; Darwin, Charles, -- 1809-1882.; Evolution (Biology) -- Great Britain -- History -- 19th century; Religion and science -- Great Britain -- History -- 19th century; Great Britain -- Intellectual life -- 19th century; SCIENCE / History; Electronic books